Effect of health locus of control on the quality of life among hemodialysis patients - Mahdi Moshki; Jahanshir Tavakolizadeh; Mohammad Vahedian Shahroodi; Mahmoud Nabiansani; Atefeh Dehnoalian (Wolters Kluwer Medknow Publications, 2021)
Objective: The purpose of this study was to determine the effect of health locus of control on the quality of life on hemodialysis patients. Materials and Methods: This study is a randomized controlled trial. Participants were 78 dialysis patients among 17-70 years old including 39 cases in the training program and 39 cases in control groups. Kidney disease quality of life-short form and the health locus of control scale-form A were used. Questionnaires were completed before and 8 weeks after the intervention by two groups. Results: The results of the paired t-test showed that the mean scores of physical component summary, mental component summary, and components of renal disease in the test group increased significantly after the intervention. There was also a significant difference between the test and control groups only about powerful others. Conclusion: The education based on health locus of control can have a positive effect on the life quality of hemodialysis patients.